Mechanical Properties and Corrosion Behavior of Ti6Al4V Particles Obtained by Implantoplasty: An In Vitro Study. Part II - Jorge Toledano-Serrabona (MDPI AG, 2021)
In the field of implant dentistry there are several mechanisms by which metal particles can be released into the peri-implant tissues, such as implant insertion, corrosion, wear, or surface decontamination techniques. The aim of this study was to evaluate the corrosion behavior of Ti6Al4V particles released during implantoplasty of dental implants treated due to periimplantitis. A standardized protocol was used to obtain metal particles produced during polishing the surface of Ti6Al4V dental implants. Physicochemical and biological characterization of the particles were described in Part I, while the mechanical properties and corrosion behavior have been studied in this study. Mechanical properties were determined by means of nanoindentation and X-ray diffraction. Corrosion resistance was evaluated by electrochemical testing in an artificial saliva medium. Corrosion parameters such as critical current density (icr), corrosion potential (ECORR), and passive current density (iCORR) have been determined. The samples for electrochemical behavior were discs of Ti6Al4V as-received and discs with the same mechanical properties and internal stresses than the particles from implantoplasty. The discs were cold-worked at 12.5% in order to achieve the same properties (hardness, strength, plastic strain, and residual stresses). The implantoplasty particles showed a higher hardness, strength, elastic modulus, and lower strain to fracture and a compressive residual stress. Resistance to corrosion of the implantoplasty particles decreased, and surface pitting was observed. This fact is due to the increase of the residual stress on the surfaces which favor the electrochemical reactions. The values of corrosion potential can be achieved in normal conditions and produce corroded debris which could be cytotoxic and cause tattooing in the soft tissues.